2017
DOI: 10.3389/fphar.2017.00626
|View full text |Cite
|
Sign up to set email alerts
|

Nardosinone Suppresses RANKL-Induced Osteoclastogenesis and Attenuates Lipopolysaccharide-Induced Alveolar Bone Resorption

Abstract: Periodontitis is a chronic inflammatory disease that damages the integrity of the tooth-supporting tissues, known as the periodontium, and comprising the gingiva, periodontal ligament and alveolar bone. In this study, the effects of nardosinone (Nd) on bone were tested in a model of lipopolysaccharide (LPS)-induced alveolar bone loss, and the associated mechanisms were elucidated. Nd effectively suppressed LPS-induced alveolar bone loss and reduced osteoclast (OC) numbers in vivo. Nd suppressed receptor activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…In the present study, it was observed that silencing of AQP5 inhibited ERK1/2 signaling, consistent with the observations of prior studies (17,36). The downstream ERK signaling proteins c-Fos and CREB, which are present in the eukaryotic nucleus, are phosphorylated upon the activation of ERK signaling (37). The current study results also demonstrated that AQP5 silencing reduced the protein levels of c-Fos and p-CREB.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, it was observed that silencing of AQP5 inhibited ERK1/2 signaling, consistent with the observations of prior studies (17,36). The downstream ERK signaling proteins c-Fos and CREB, which are present in the eukaryotic nucleus, are phosphorylated upon the activation of ERK signaling (37). The current study results also demonstrated that AQP5 silencing reduced the protein levels of c-Fos and p-CREB.…”
Section: Discussionsupporting
confidence: 92%
“…30,31 LPS stimulates NF-kB activation and then leads to the release of inflammatory cytokines including TNF-α and IL-1, which induces osteoclast differentiation and function. 31,36 Our results demonstrated that daidzin greatly reduced bone resorption and TRAP-positive osteoclast number induced by LPS administration. Therefore, the inhibition of LPS-stimulated bone destruction could be attributed to the ability of daidzin to suppress NF-ĸB signaling activation.…”
Section: Discussionmentioning
confidence: 60%
“…Based on these theories, a dose-dependent decrease in the number of TRAP +ve osteoclasts suggests a direct inhibitory effect of C-PC on the RANKL-induced osteoclastogenesis. This assay is considered the primary tool to investigate whether a non-cytotoxic compound has an anti-osteoclastogenic activity or not [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%